Formulation Of Plant Based Cooling Agent From Peppermint Oil - Sharip, Norazreen; Nordin, Norain; Mazelan, Nur Azian; Zubairi, Zarif Syazani; Zainudin, Siti Asma’ (Multidisciplinary Applied Research and Innovation, 2021)
Cooling agent are widely used in wide range of products ranging. It helps to give cooling and fresh sensation and specific sensory toward human’s skin. Usually, cooling agent are related with menthol as the only compound that can act as a cooling sensation when applied to skin. The major effects of menthol is to cause a sensation of coolness. The sensation of cold or warmth is determined by the activity of thermoreceptors in the human’s skin and mucosal surfaces. These cold and warm receptors are considered to be free nerve endings without any specialized end organ. Menthol are derived from peppermint because it has a high menthol content. In this project, the combination of organic plants that is cucumber, aloevera and peppermint are used in the formulation of cooling agent. The best solution of cooling agent shows the time taken cold effect last on skin is longest and time taken needed for sample starts to cold on skin is shortest. Extraction using steam distillation process toward 5000 g fresh peppermint leaves are done to produce peppermint oil. Aloevera are extract directly from their inner gel and cucumber are extract using boiling process. By using Gas Chromatography, peppermint oil composition is determined. The formulation solution of cooling agent then are tested to analyse the cooling and refreshing effect to fifteen respondents. Sample A consist of peppermint oil, cucumber extract and aloevera gel, sample B consist of aloevera and cucumber and sample C consists of peppermint only. From the result of Gas Chromatography indicate peak of menthol in peppermint oil at retention time 11.1 minutes. It shows the present of menthol compound . The feedback form resulted the time taken for cold effect last on skin and time taken needed for sample starts to cold on skin for sample A are 31.93 minutes and 4.73 minutes, 3.8 minutes and 13.6  minutes for sample B and 28.6 minutes and 8.4 minutes for sample C respectively. As the conclusion, the combination of peppermint oil, cucumber extract and aloevera gel from sample A gives the best result as a cooling agent.